Individual, Family and Abuse Characteristics of 700 British Child and Adolescent Sexual Abusers. (27th February 2013) - Hackett, Simon; Phillips, Josie; Masson, Helen; Balfe, Myles
Abstract : The individual, family and abuse characteristics of 700 children and young people referred to nine UK services over a nine‐year period between 1992 and 2000 as a result of their sexually abusive behaviours were examined. The most common age at referral was 15 years, though a third of all referrals related to children aged 13 or under. Thirty‐eight per cent of the sample were identified as learning disabled. Surprisingly high rates of sexual and non‐sexual victimisation were present in the backgrounds of the children and young people referred. A wide range of abusive behaviours was perpetrated with just over half of the sample having penetrated or having attempted to penetrate another individual. Victims were usually known to the abuser but in 75 per cent of cases were not related. Fifty‐one per cent of the sample abused females only, though 49 per cent had at least one male victim. The implications for policy and practice with children and young people with harmful sexual behaviours are discussed. Copyright © 2013 John Wiley & Sons, Ltd. 'Thirty‐eight per cent of the sample were identified as learning disabled' Key Practitioner Messages: Children and young people who sexually abuse others are a diverse group with a complex set of motivations, background experiences and varying types of abusive behaviour. Children and young people with learning disabilities who sexually abuse comprise a particularly vulnerable group with specific intervention needs. A one‐size‐fits‐all intervention approach is not appropriate, but child‐centred services that focus on both care and control aspects are warranted. 'A one‐size‐fits‐all intervention approach is not appropriate'